Implementasi Metode Ceramah dan Tanya Jawab Pada Mata Kuliah Microteaching Mahasiswa Universitas Sunan Giri Surabaya - Shidiq, Shidiq; El-Yunusi, Muhammad Yusron Maulana (CV. Satria Jaya, 2024)
Teaching skills are specific abilities that must be possessed by teachers or prospective teachers in order to carry out teaching tasks efficiently, professionally and effectively. The purpose of this study was to determine the ability of postgraduate students of Sunan Giri University Surabaya in teaching about Islamic Religious Education material. This research uses a qualitative approach. Data collection techniques were conducted through interviews, observation, and documentation. Researchers conducted the process of collecting, reducing, and concluding data through triangulation techniques. The results showed that the implementation of the lecture and question and answer method in the microteaching program of Islamic Education Postgraduate students at Sunan Giri University Surabaya was divided into three activities, namely the first initial activity includes conveying learning objectives and managing student attention and conditions, the second core activity includes presentation of material, providing opportunities for questions and answers between students and providing conclusions and the third final activity includes conducting evaluations. Among the advantages is that the lecture method is very effective when the number of students is larger. In addition, the lecture and question and answer method applied in this program also has shortcomings including students getting bored easily so that as a step taken, namely by using audio-visual learning media as a support for the process of implementing the microteaching program.